PHYTOCHEMICAL CHARACTERIZATION OF TWELVE MEDICINAL PLANTS USED FOR SICKLE CELL DISEASE MANAGEMENT IN CHHATTISGARH - AKRITI GUPTA; SHUBHANGI SHARMA; HENU KUMAR VERMA; DIVYA SUDHIR TYAGI; PANKAJ KISHOR MISHRA; P K PATRA (International Journal of Pharma and Bio Sciences, 2015)
Medicinal plants can be a source of succour in the control of sickle cell disease (SCD) in Chhattisgarh. The lower strata of the state rely heavily on traditional medicine due to their cultural alignment as well as their inability to afford the cost of treatment offered by orthodox medical practitioners. Twelve plant species have been selected to examine their phytochemical constituents from SCD prone areas of state currently used to the management of disease. Qualitative analysis of phytochemical constituents’ viz. tannins, flavonoids, terpenoids, saponins, phenol, steroids, phlobatannins, carbohydrates, glycosides, coumarins, alkaloids, proteins, emodins, anthraquinones, anthocyanins, leucoanthocyanins and quantitative analysis of alkaloids, tannin, saponins, flavonoids and total phenol was performed by the standard protocol available in the literature. Quantitative analysis of alkaloid, tannin, saponin, flavonoids and total phenol had revealed that Momordica charantia possessed maximum alkaloid (5.92%w/w) and tannin (9.44%w/w), Aloe vera highest saponin (7.15%w/w) & flavonoids (8.23%w/w) and Allium sativum highest total phenol (12.43%w/w) content. Present findings will be very compassionate to elaborate our study objectives to investigate better management options and reduce the symptomatic crisis of SCD.